Предмет: Алгебра,
автор: lalabai1
номер 57. решите, пожалуйста
Приложения:
Ответы
Автор ответа:
0
b1=1,b2=-tgπ/6⇒b2=-1/√3⇒q=b2/b1=-1/√3
S=b1/(1-q)
S=1:(1+1/√3)=1:(√3+1)/√3=√3/(√3+1)=√3*(√3-1)/[(√3+1)(√3-1)]=
=√3(√3-1)/(3-1)=√3(√3-1)/2
S=b1/(1-q)
S=1:(1+1/√3)=1:(√3+1)/√3=√3/(√3+1)=√3*(√3-1)/[(√3+1)(√3-1)]=
=√3(√3-1)/(3-1)=√3(√3-1)/2
Похожие вопросы
Предмет: Биология,
автор: serebryanskaya235
Предмет: Английский язык,
автор: wssxws
Предмет: Математика,
автор: supermichei
Предмет: Физика,
автор: galn43
Предмет: Биология,
автор: ученая5